2012
DOI: 10.1093/ehjci/jes156
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of global longitudinal strain for predicting early outcome after cardiac surgery

Abstract: GLS has an incremental value over LVEF for risk stratification in patients referred for cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 20 publications
0
57
1
2
Order By: Relevance
“…A previous study reported an association between impaired LV-GLS and mortality; however, only 23% of these patients underwent MV surgery. 24 Another study using rest and stress echocardiography reported a higher event rate (death, MV surgery, and heart failure admissions) in patients with an abnormal GLS contractile reserve. 25 The current study had a significantly larger sample size and a much longer follow-up with a hard end point of mortality, along with studying the sequentially incremental impact of LV-GLS and BNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported an association between impaired LV-GLS and mortality; however, only 23% of these patients underwent MV surgery. 24 Another study using rest and stress echocardiography reported a higher event rate (death, MV surgery, and heart failure admissions) in patients with an abnormal GLS contractile reserve. 25 The current study had a significantly larger sample size and a much longer follow-up with a hard end point of mortality, along with studying the sequentially incremental impact of LV-GLS and BNP.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] However, prognostic data regarding the role of LV-GLS in MR patients is sparse. 24,25 Furthermore, to the best of our knowledge, the potential additive value of BNP and LV-GLS in risk stratification of patients with significant MR who underwent MV surgery has not been previously studied. In a contemporary population of asymptomatic patients with significant MR and preserved LVEF who underwent MV surgery, we sought to determine whether baseline LV-GLS and BNP (1) were associated with a reduction in postoperative LVEF and (2) provided incremental prognostic utility over conventional measures previously shown to affect outcome in this condition.…”
mentioning
confidence: 99%
“…This was further confirmed in a prospective study of 425 patients referred for cardiac surgery. 9 This study demonstrated that GLS was an independent predictor, superior to EF, for early postoperative mortality after adjustment to EuroSCORE. In an era of multimodality imaging, it is important to know how values compare between imaging modalities.…”
Section: Myocardial Functionmentioning
confidence: 57%
“…19 Despite similar surgical risk EuroSCORE, the postoperative death rate was significantly higher and 2.4-fold increased in patients with abnormal global longitudinal strain even in preserved ejection fraction. 20 Long isovolumic time (odds ratio 1.37, P = 0.035) predicts adverse cardiac events after CABG. 21 We observed similar EuroSCORE in both good and poor outcome groups.…”
Section: Discussion-mentioning
confidence: 98%